EFEKTIFITAS EDUKASI KESEHATAN MENGGUNAKAN MEDIA LEAFLET TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG ANEMIA DI SMKS PERIKANAN AL-ITTIHADIYAH KABUPATEN ROKAN HILIR - Isnaini, Isnaini; Lisviarose, Lisviarose; Tanberika, Fajar Sari; Mardiya, Rizka (Ensiklopedia of Journal, 2026)
Adolescent girls are a group that is vulnerable to anemia due to lack of knowledge about anemia and its prevention. Data from SMKS Fisheries Al-Ittihadiyah Rokan Hilir Regency shows that 3 adolescent girls often feel sleepy while studying, while 7 adolescent girls feel weak and dizzy during menstruation. One way to prevent anemia in adolescent girls is to increase knowledge about anemia through providing health education using leaflets. The study aims to determine the effectiveness of health education using leaflets on adolescent girls' knowledge about anemia at SMKS Fisheries Al-Ittihadiyah Rokan Hilir Regency. This type of research is quantitative with a quasi-experimental approach, pre-test and post-test. The population is 43 adolescent girls, the sample is 43 respondents. Sampling uses a total sampling technique. The research instrument is a questionnaire. Data are analyzed using the Dependent T-test. The results of the study showed that before health education using leaflets, there were more respondents with low knowledge, namely 83.7%. After health education using leaflets, there were more respondents with high knowledge, namely 88.4%. There is effectiveness of health education using leaflets on adolescent girls' knowledge about anemia (P = 0.000). It is recommended that schools also collaborate with community health centers (Puskesmas) to conduct regular health education activities using leaflets to ensure all students have a strong understanding of anemia and its prevention.Keywords: Health Education, Leaflets, Adolescent Girls' Knowledge, Anemia